Remote Sensing and GIS for Surface Water Resources in Rawa Biru – Torasi Merauke Papua - Hartono Hartono; Barano SS Meteray; Nur Mohammad Farda; Muhammad Kamal (Universitas Muhammadiyah Surakarta, 2006)
The research describe about surface water ecosystem study in Merauke Papua by using multisource and multistage remote sensing data which was splitted into two parts based on the study areas. First, it is for micro scale spatial analysis focusing on the Rawa Biru – Torasi watershed, while the second is for macro scale spatial analysis for Transfly ecoregionin the floodplain areas of Merauke. Multispectral approach was adopted for Landsat image analysis, followed by field survey on the selected areas. Auxilary data used are maps, secondary documents in order to improve understanding of the areas. Interview and discussion with related institutions (Wasur National Sanctuary, Potable Water Services, Internal Affairs Government, Forestry Service) accordingly were carried out. The research result showed that remote sensing imagery are usefull for surface water resources study. Physical condition of the Rawa Biru – Torasi watershed, vegetation analysis by using multitemporal data, wetland type, hydrological process in the floodplain were presented. Rawa Biru watershed as a resource for drinking water supply environmentaly decreased considerably due to the species invasion, with successively dominated by hydrophilla, tebu rawa, rumput pisau, dan Mellaleuca and sedimentation took place in the main body of swamp. Upper part of the watershed is actually included in the Papua New Guinea, in long water resources development scheme, it need administratively belong to one recharge areas for the watershed.